Synergy of Digitalization within the Framework of Increasing Energy Efficiency in Manufacturing Industry - Shinkevich, Marina V.; Vertakova, Yulia V.; Galimulina, Farida F. (International Journal of Energy Economics and Policy, 2020)
The article contains the results of the study of manufacturing industry in terms of energy efficiency, digitalization and ecology. Interdependencies of the listed aspects are established and the synergetic effect of digitization is determined with the help of economic and mathematical modeling. Digital technologies are now being adopted with care by industrial enterprises, which has resulted in a high potential for digitalization that has not been realized so far. In this regard, there are untapped opportunities to improve the energy efficiency of manufacturing operations and to ensure the principles of sustainable development, which determines the relevance of this study. The aim of the study is to determine the synergistic effect of digitalization, taking into account the improvement of energy efficiency and environmental protection of manufacturing. The key research methods were the methods of comparison and description, which made it possible to assess the dynamics of the efficiency of energy consumption in the industry; vertical dynamic analysis, reflecting the change in the structure of energy consumption over time; correlation and regression analysis, which established a mathematical relationship between the analyzed factors and reflects the influence of the selected factors; a forecasting method that determines the change in the values of predictor variables in future periods; optimization method, which allowed to find the optimal values of energy consumption in the manufacturing sector of the economy. As a result of application of these methods, the article reflected the results of an analysis of the dynamics of energy consumption by manufacturing enterprises of the Russian economy; economic and mathematical models are proposed in the form of multiple linear regression equations that describe the dependence of environmental and “digital” parameters on energy efficiency indicators, allowing varying independent variables in order to achieve specific values of the resulting indicator; a model for optimizing energy consumption and financing energy efficiency was developed with the condition of minimizing polluting emissions by the manufacturing industry and further digitalizing of the industry. The research materials reflected in the article can be taken into account and applied within the framework of forming strategies and programs to ensure energy efficiency in manufacturing industries, their sustainable development and digitalization of production processes and the formation of digital platforms for interaction with external actors. Keywords: energy resources, energy efficiency, manufacturing sector of economy, digitalization, sustainable development, ecology, forecasting, optimization model. JEL Classifications: L23, M11, Q43, Q52 DOI: https://doi.org/10.32479/ijeep.9397